Marketing Strategy of Local Wisdom SMEs Roti Durian Panglima - Ivan armawan; Sudarmiatin Sudarmiatin (Eduvest - Journal of Universal Studies, 2021)
Samarinda is the capital city of the province of East Kalimantan. The city government of Samarinda has been set to utilize and develop the potential of the development of the economy of regions based on natural resources. This article aims to explore the potential effect of natural resources, namely durian fruit in the region melak, to be developed into a product featured locally by formulating its development strategy to be able to compete in the world of business SMEs. The method used in this article is a qualitative approach. The selection of  Durian Panglima Bread SMEs as an object of research is based on local wisdom, which is used as raw material in marketed products so as to introduce local potentials. Data collection based on primary data and secondary data that the author has done. Observations were made at the  Durian Panglima Bread SMEs outlets in the cities of Balikpapan and Samarinda. the results of this study concluded that the use of local wisdom by looking at existing natural resources can provide much better potential in terms of product development, which can create jobs and prosper the people. In an effort to develop products for UKM Durian Panglima Bread, it takes a long process to reach the current point with 11 outlets and two outlets.The very rapid development of SMEs with high competitiveness requires UMKM Roti Durian Panglima to carry out several marketing strategies, namely the order system, resellers at the beginning of its product, to opening branches in several places. However, it cannot be separated from the technology system to accelerate the process of spreading the brand image through social media. Also, it requires UKM Durian Panglima Bread to innovate its products with new fillings so that customers feel more interested.